ZnO Nanoparticles: Exposure, toxicity mechanism and assessment. (2022) - Nagar, Varad; Singh, Tanvi; Tiwari, Yamini; Aseri, Vinay; Pandit, Pritam P; Chopade, Rushikesh L; Pandey, Kamakshi; Lodha, Payal; Awasthi, Garima
Graphical abstract: Abstract: Recently, ZnO NPs have been widely used in cosmetics, rubber, medicine, chemical fiber, electronics, and other industries due to their large surface area and enhanced redox capacity. ZnO nanoparticles show biological toxicity in various organisms such as algae, plants, vertebrates, invertebrates, and microorganisms. The presence of ZnO NPs in the natural environment can pose a threat to humans as well. So, ZnO NP's appearance in nature and their assessment of toxicity have become yet another activity. The current review covers the effects of ZnO NPs on various living organisms like plants, invertebrates, vertebrates, and mammalian cells. In order to comprehensively evaluate the environmental risk of ZnO NPs and realize the safety management of ZnO NPs, different perspectives are put forward for future toxicity studies. Another focus of this paper is to interpret what are the various exposure methods by which ZnO NPs enter any living system and to what extent it damages the cell and leads to apoptosis.